Diverging regional climate preferences and the assessment of solar geoengineering - Pfrommer, Tobias (Discussion paper series, 2018)
Solar Geoengineering (SG) is a set of potential technologies to counteract climate change. While SG can only imperfectly compensate for temperature changes at the regional level, studies assessing regional SG impacts indicated so far that regional temperature disparities from SG may not be as severe as previously thought. A shortcoming of that literature is its assumption that regions’ temperature preferences correspond to some historic baseline climate. I extend the main framework for examining regional SG impacts by allowing for regions to have temperature preferences diverging from the baseline climate, showing that the impact of these diverging preferences can be split into two components. The first component changes the optimal SG level, but does not affect regional disagreement over SG. The second component leaves the optimal SG level unaffected, but changes regional disagreement over SG. I identify three aspects of SG performance in the presence of diverging preferences. A numerical implementation of the extended model shows that the presence of diverging preferences may change SG performance in either direction and that the direction generally depends on which of the three aspects of SG performance is considered.